Bispecific antibodies targeting CTLA-4: game-changer troopers in cancer immunotherapy - Farhangnia, Pooya; Ghomi, Shamim Mollazadeh; Akbarpour, Mahzad; Delbandi, Ali-Akbar (Frontiers in Immunology, 2023)
Antibody-based cancer immunotherapy has become a powerful asset in the arsenal against malignancies. In this regard, bispecific antibodies (BsAbs) are a ground-breaking novel approach in the therapy of cancers. Recently, BsAbs have represented a significant advancement in improving clinical outcomes. BsAbs are designed to target two different antigens specifically. Over a hundred various BsAb forms currently exist, and more are constantly being manufactured. An antagonistic regulator of T cell activation is cytotoxic T lymphocyte-associated protein 4 (CTLA-4) or CD152, a second counter-receptor for the B7 family of co-stimulatory molecules was introduced in 1996 by Professor James P. Allison and colleagues. Contrary to the explosive success of dual immune checkpoint blockade for treating cancers, a major hurdle still yet persist is that immune-related adverse events (irAEs) observed by combining immune checkpoint inhibitors (ICIs) or monoclonal antibodies such as ipilimumab (anti-CTLA-4) and nivolumab (anti-PD-1). A promising strategy to overcome this hurdle is using BsAbs. This article will summarize BsAbs targeting CTLA-4, their applications in cancer immunotherapy, and relevant clinical trial advances. We will also discuss the pre-clinical rationale for using these BsAbs, and provide the current landscape of the field.